MANAJEMEN BADAN AMIL ZAKAT NASIONAL MANDAILING NATAL DALAM PENGELOLAAN ZAKAT: STAIN Mandailing Natal - Rukiah Rukiah; RUKIAH DAN SYAHRIAL DEDI (Program Studi Perbankan Syariah Jurusan Syariah, Ekonomi dan Bisnis Islam Sekolah Tinggi Agama Islam Negeri Mandailing Natal (STAIN MADINA), 2020)
Abstract Management of the Mandailing Natal National Zakat Board in the Management of Zakat. This journal discusses the management of the Mandailing Natal National Zakat Agency in managing the management. The research method used is field research with a qualitative approach, namely seeking information about the management of the National Zakat Agency of Mandailing Natal Regency in collecting and distributing zakat, by collecting primary data and secondary data as well as from other related materials, analyzing the results of data processing and making interpretation and conclusion. Based on the results of research conducted at the Mandailing Natal Regency National Amil Zakat Board, it can be concluded that the management carried out by the Mandailing Natal Regency National Amil Zakat Board in collecting and distributing zakat still needs to be improved. Based on its implementation, Baznas Mandailing Natal with the main task of collecting and utilizing and distributing zakat, infaq and shodaqoh funds for Muslims in Mandailing Natal Regency has a program with the aim of making people prosperous. Keywords: Management, Zakat, National Zakat Agency